The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ibd.20963
|View full text |Cite
|
Sign up to set email alerts
|

PepT1 oligopeptide transporter (SLC15A1) gene polymorphism in inflammatory bowel disease

Abstract: A functional polymorphism in the SLC15A1 gene might be of relevance to inflammation and antibacterial responses in IBD. Whether this polymorphism truly contributes to disease susceptibility needs to be further addressed, and should stimulate additional studies in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Recent studies have linked IBD to either polymorphisms in genes encoding SLC15 family members (35) or changes in the intestinal expression of SLC15 proteins (36). Because of the implication of NOD1 and NOD2 in IBD, we aimed to identify whether the mRNA expression levels of SLC15A4 were altered in the intestine of IBD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have linked IBD to either polymorphisms in genes encoding SLC15 family members (35) or changes in the intestinal expression of SLC15 proteins (36). Because of the implication of NOD1 and NOD2 in IBD, we aimed to identify whether the mRNA expression levels of SLC15A4 were altered in the intestine of IBD patients.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort of IBD patients and ethnically matched controls from Sweden has been previously described in detail (34)(35)(36)(37). For the specific purpose of this study, 618 CD patients, 630 UC patients, and 630 blood donor controls have been included.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, our studies have revealed that PepT1 may be involved in the pathogenesis of IBD in humans. 17,49,50 However, a direct role of PepT1 in immune cells during intestinal inflammation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%